Nanoparticles design considerations to co-deliver nucleic acids and anti-cancer drugs for chemoresistance reversal - Sahar Eljack; Stephanie David; Areeg Faggad; Igor Chourpa; Emilie Allard-Vannier (Elsevier, 2022)
Chemoresistance and hence the consequent treatment failure is considerably challenging in clinical cancer therapeutics. The understanding of the genetic variations in chemoresistance acquisition encouraged the use of gene modulatory approaches to restore anti-cancer drug efficacy. Many smart nanoparticles are designed and optimized to mediate combinational therapy between nucleic acid and anti-cancer drugs. This review aims to define a rational design of such co-loaded nanocarriers with the aim of chemoresistance reversal at various cellular levels to improve the therapeutic outcome of anticancer treatment. Going through the principles of therapeutics loading, physicochemical characteristics tuning, and different nanocarrier modifications, also looking at combination effectiveness on chemosensitivity restoration. Up to now, these emerging nanocarriers are in development status but are expected to introduce outstanding outcomes.